Ursus arctos subsp. horribilis Ord 1815 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Ursus arctos subsp. horribilis Ord 1815 Synonyms: Ursus arctos subsp. absarokus Merriam 1914; Ursus arctos subsp. andersoni Merriam 1918; Ursus arctos subsp. apache Merriam 1916; Ursus arctos subsp. arizonae Merriam 1916; Ursus arctos subsp. bairdi Merriam 1914; Ursus arctos subsp. bisonophagus Merriam 1918; Ursus arctos subsp. canadensis Merriam 1914; Ursus arctos subsp. candescens C. E. H. Smith 1827; Ursus arctos subsp. cinereus Desmarest 1820; Ursus arctos subsp. crassus Merriam 1918; Ursus arctos subsp. dusorgus Merriam 1918; Ursus arctos subsp. ereunetes Merriam 1918; Ursus arctos subsp. griseus Choris 1822; Ursus arctos subsp. horriaeus Baird 1858; Ursus arctos subsp. hylodromus Elliot 1904; Ursus arctos subsp. idahoensis Merriam 1918; Ursus arctos subsp. imperator Merriam 1914; Ursus arctos subsp. impiger Merriam 1918; Ursus arctos subsp. inopinatus Merriam 1918; Ursus arctos subsp. kennerleyi Merriam 1914; Ursus arctos subsp. kluane Merriam 1916; Ursus arctos subsp. latifrons Merriam 1914; Ursus arctos subsp. macfarlani Merriam 1918; Ursus arctos subsp. macrodon Merriam 1918; Ursus arctos subsp. mirus Merriam 1918; Ursus arctos subsp. navaho Merriam 1914; Ursus arctos subsp. nelsoni Merriam 1914; Ursus arctos subsp. ophrus Merriam 1916; Ursus arctos subsp. oribasus Merriam 1918; Ursus arctos subsp. pallasi Merriam 1916; Ursus arctos subsp. pellyensis Merriam 1918; Ursus arctos subsp. perturbans Merriam 1918; Ursus arctos subsp. planiceps Merriam 1918; Ursus arctos subsp. pulchellus Merriam 1918; Ursus arctos subsp. richardsoni Swainson 1838; Ursus arctos subsp. rogersi Merriam 1918; Ursus arctos subsp. rungiusi Merriam 1918; Ursus arctos subsp. russelli Merriam 1914; Ursus arctos subsp. sagittalis Merriam 1918; Ursus arctos subsp. selkirki Merriam 1916; Ursus arctos subsp. shoshone Merriam 1914; Ursus arctos subsp. texensis Merriam 1914; Ursus arctos subsp. utahensis Merriam 1914; Ursus arctos subsp. washake Merriam 1916. Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Carnivora, ...